Chapter 13 Commemorating vanished 'homelands' Displaced Germans and their Heimat Europa - Kockel, Ullrich (Taylor & Francis, 2019)
The twentieth century has been described (e.g., Piskorski 2015 ) as a century of displacement. While globally the comparative scale of involuntary population movement may not have diff ered signifi cantly from earlier centuries, its perception has changed radically, leading in the early twenty- fi rst century to the dramatic resurgence of xenophobic populism across Europe and beyond (see Kaya 2017 ; De Cesari and Kaya 2019). Throughout the 'refugee crisis' of the 2010s, the German government's moderate policy towards new migrants was widely criticised. The ideological foundation for that policy was, arguably, the country's experience of integrating millions of ethnic German expellees and refugees from Central and Eastern Europe in the aftermath of the Second World War.